Stock Prices in Banking: Profitability, Capital, Firm Value, and Company Size.: Harga Saham di Sektor Perbankan: Profitabilitas, Struktur Modal, Nilai Perusahaan, dengan Ukuran Perusahaan sebagai Variabel Moderasi - Tri Wahyuni; Nurasik (Universitas Muhammadiyah Sidoarjo, 2024)
The study aimed to assess factors influencing stock prices in Indonesian banking firms from 2018-2020. Using quantitative methods with a sample of 15 companies from the Indonesia Stock Exchange, the research found that profitability positively and significantly affects stock prices. However, capital structure and firm value showed no direct impact. Firm size was identified as a positive and significant influencer of stock prices. Notably, firm size moderated the effect of firm value on stock prices, but it didn't moderate profitability or capital structure's impact on stock prices. Highlights: Profitability Matters: The study emphasizes that profitability has a positive and significant impact on stock prices, highlighting the crucial role of a company's financial performance in influencing investor perception and market valuation. Size Does Matter: The size of a company plays a key role, with firm size demonstrating a positive and significant effect on stock prices. Additionally, firm size is identified as a moderator, influencing the relationship between firm value and stock prices. Capital Structure's Limited Impact: Contrary to profitability and firm size, the study suggests that capital structure alone does not significantly affect stock prices. This finding underscores the nuanced nature of factors influencing stock market dynamics. Keywords: Stock Price, Profitability, Capital Structure, Firm Value